2023
DOI: 10.31234/osf.io/xt5qe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-control and grit are associated with school performance mainly because of shared genetic effects

Abstract: Background: By combining the classical twin design with regression analysis, we investigated the role of two non-cognitive factors, self-control and grit, in the prediction of school performance. We did so at the phenotypic, genetic, and environmental level. Methods: Teachers filled out a survey on the twins’ school performance (school grades for reading, literacy, and math), self-control (ASEBA self-control scale), and grit (the perseverance aspect) for 4,891 Dutch 12-years-old twin pairs (3,837 pairs with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…cognitive skills or intelligence), as measured by cognitive tests. Cognitive performance is known to be correlated to educational achievement and attainment between 0.4 and 0.8 [17][18][19][20] , sharing large overlapping genetic influences (genetic correlations ~ 0.7) [21][22][23] . Though it should be noted the relation between cognition and education is likely bidirectional 24 , higher cognitive performance increases educational opportunities.…”
Section: Noncognitive Aspects Of Educational Attainmentmentioning
confidence: 99%
“…cognitive skills or intelligence), as measured by cognitive tests. Cognitive performance is known to be correlated to educational achievement and attainment between 0.4 and 0.8 [17][18][19][20] , sharing large overlapping genetic influences (genetic correlations ~ 0.7) [21][22][23] . Though it should be noted the relation between cognition and education is likely bidirectional 24 , higher cognitive performance increases educational opportunities.…”
Section: Noncognitive Aspects Of Educational Attainmentmentioning
confidence: 99%
“…As reported in Kevenaar et al (2023), we previously analysed teacher ratings of grit, self-control, and school performance in MZ and DZ twins using the same data that were analysed for the present article. The results were obtained with a correction for the main effects of sex and SES, and a correction for the rater (i.e., the teacher of the twins).…”
Section: Previous Findingsmentioning
confidence: 99%
“…In a twin study, Kevenaar et al (2023) found that grit and self-control together explained 28.4% of the variance in school performance. The decomposition of the phenotypic regression relationships into genetic and environmental components revealed that the phenotypic associations were mainly due to genetic factors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations